Post intubation Pharyngolaryngeal Pain in Otorhinolaryngology Surgery: Efficiency of Intra cuff and Extra cuff Lidocaine - Hafiane Reda; Lazraq Mohamed; Bensaid Abdelhak; Miloudi Youssef; El Harrar Najib (Research and Practice in Anesthesiology, 2018)
Introduction Post-operative sore throat (POST) represents a real discomfort for patients. In short duration surgeries, sore throat complain can replace the post-operative pain. Many studies intended to reduce its incidence using multiples medications. Objective Assess the efficiency of extra cuff lidocaine jelly 2% associated with intra cuff liquid lidocaine 2% on the post extubation syndrome. Materials and method Prospective study lead during 3 months in Otorhinolaryngology operating rooms. Inclusion criteria: Every intubation (naso or orotracheal) performed during this period. Exclusion criteria: upper airways surgery, tonsillectomy and patient’s refusal. Patients were randomized in 3 groups: First (G1): Control group (inflated cuff with air), Second (G2): liquid lidocaine 2% injected intracuff, Third (G3): Lidocaine 2% jelly applied on the external surface of the cuff associated with liquid lidocaine intra cuff. Patients were assessed for post-operative sore throat, cough, and hoarseness at 1, 6, and 24 hours after surgery. Results Ninety-nine patients were randomized (G1 n=30, G2 n=34, G3 n=35). The association of liquid and jelly lidocaine reduced POST at H1, H6, and H24 after patient’s discharge (p respectively at 0.0001; 0.002; 0.003 and 0.004). There was no significant difference in blunting coughing (p=0.053) and post-operative nausea and vomiting (p=0.198). Conclusion The association of liquid and jelly lidocaine was efficient in reducing the POST. This result needs to be supported by a larger study including an important number of patients.